2007
DOI: 10.1111/j.1399-3038.2007.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of measles vaccination on the progression of atopic dermatitis in infants

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease, affecting 10-20% of children. Measles vaccination has been reported to have contradictory effects on incidence of AD in children. Therefore, we performed the first prospective, double-blind, placebo-controlled study to analyze the evolution of AD in infants after measles vaccination. The study included 12 infants (10-14 months old) with AD, randomly assigned to two groups: while the first group received a single dose of a standard measles vaccine R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…PARC is a dendritic cell‐derived chemokine up‐regulated in AD that mediates skin homing of human memory T cells . Furthermore, significant decrease of PARC was observed in AD after immunotherapy . Increased gene expression of PARC was reported in PS, although to a lesser extent than AD .…”
Section: Discussionmentioning
confidence: 99%
“…PARC is a dendritic cell‐derived chemokine up‐regulated in AD that mediates skin homing of human memory T cells . Furthermore, significant decrease of PARC was observed in AD after immunotherapy . Increased gene expression of PARC was reported in PS, although to a lesser extent than AD .…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have also shown a beneficial effect of MCV on childhood survival, the effect being greater when MCV are given before the age of 12 months . The immunomodulatory effects of MCV have also been used in the treatment of atopic dermatitis, for which the vaccine (given subcutaneously) has been reported to decrease serum immunological markers . In addition, in the treatment of cutaneous warts, it been hypothesized that the injection of MCV into lesions accelerated the destruction of the papilloma virus and infected host cells …”
Section: Introductionmentioning
confidence: 99%
“…There are ever more publications on immunizations and atopy risk. Our latest paper falls into line with the ground swell of opinion that there is no impact, in this case focused on MMR (11,12). The sequence of immunizations normally separates live attenuated vaccines from others.…”
mentioning
confidence: 61%